Das Christentum im frühen Europa: Diskurse - Tendenzen - Entscheidungen - Heil, Uta (Millennium-Studien, 2019)
During the transition from late antiquity to the early Middle Ages, the geographical space of Europe was Christian and Christianity was “European.” The essays present the major theological discourses and decisions of that epoch that helped shape Church and society – from political regents to Church catechesis